Nicotinamide nucleotide transhydrogenase mRNA expression is related to human obesity12. (16th April 2013) - Heiker, John T.; Kern, Matthias; Kosacka, Joanna; Flehmig, Gesine; Stumvoll, Michael; Shang, Edward; Lohmann, Tobias; Dreßler, Miriam; Kovacs, Peter; Blüher, Matthias; Klöting, Nora
Abstract Objective: A spontaneous deletion in the nicotinamide nucleotide transhydrogenase (Nnt) gene eliminating exons 7‐11 in C57BL/6J (B6J) mice is associated with reduced glucose‐stimulated insulin secretion in vitro, impaired glucose tolerance, higher epigonadal fat mass, and altered susceptibility to diet induced obesity of male B6J mice was proposed. A potential implication for NNT in human adipose tissue distribution has not been investigated so far. Design and Methods: Therefore, NNT mRNA expression in paired human samples of visceral (vis) and subcutaneous (sc) adipose tissue from 221 subjects with a wide range of body mass index (BMI), insulin sensitivity, and glucose tolerance was analyzed. Results: NNT mRNA expression is significantly higher in visceral fat of obese patients and correlates with body weight, BMI, % body fat, visceral and sc fat area, waist and hip circumference, and fasting plasma insulin (FPI). Multivariate linear regression analysis revealed visceral NNT expression as age and gender independent predictor of BMI, waist circumference, visceral fat area, and % body fat, but not FPI and 2 h OGTT glucose. Conclusion: In conclusion, a functional relevance of NNT in the development of human obesity and visceral fat distribution was suggested here.